Invisible violence in aging - Valdés, Sandra Emma Carmona (Revista Kairós-Gerontologia, 2014)
Different areas surrounding the elderly where structural violence isexpressed, are presented in this paper, considering the factors that influence theirdevelopment, harmony and well-being; and those elements that involve the existence ofunequal access and use of the material and social resources which impact adversely ontheir quality of life. So an analysis of the actions taken by the state to reduce existinginequalities and their impact on the welfare of the elderly is also presented.